2002
DOI: 10.1107/s010827010201822x
|View full text |Cite
|
Sign up to set email alerts
|

Aqua(dipicolinato-κ3O2,N,O6)(1,10-phenanthroline-κ2N,N′)manganese(II) monohydrate

Abstract: In the title compound [systematic name: aqua(1,10-phenanthroline-kappa(2)N,N')(pyridine-2,6-dicarboxylato-kappa(3)O(2),N,O(6))manganese(II) monohydrate, [Mn(C(7)H(3)NO(4))(C(12)H(8)N(2))(H(2)O)].H(2)O, the manganese(II) centre is surrounded by one bidentate phenanthroline ligand [Mn-N = 2.248 (3) and 2.278 (3) A], one tridentate dipicolinate ligand [Mn-N = 2.179 (3) A, and Mn-O = 2.237 (2) and 2.266 (2) A] and one water molecule [Mn-O = 2.117 (3) A], and it exhibits a strongly distorted octahedral geometry, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…In the M/pydc/L system, the similar complexes [Cu(pydc)-(2,2 H -bipyridine)] (Bresciain-Pahor et al, 1985), [Mn(pydc)-(1,10-phenanthroline)] (Ma et al, 2002) and [Co(pydc)(1,10phenanthroline)] (Yin & Jiang, 2001) have been reported before. These complexes have simple discrete structures.…”
Section: Figuresupporting
confidence: 66%
“…In the M/pydc/L system, the similar complexes [Cu(pydc)-(2,2 H -bipyridine)] (Bresciain-Pahor et al, 1985), [Mn(pydc)-(1,10-phenanthroline)] (Ma et al, 2002) and [Co(pydc)(1,10phenanthroline)] (Yin & Jiang, 2001) have been reported before. These complexes have simple discrete structures.…”
Section: Figuresupporting
confidence: 66%
“…The Mn atom, atoms O1 and N2, and the inversion-related O/N-atom pair are strictly coplanar as a result of the Mn atom lying on the inversion centre. The two O atoms of the symmetry-related water molecules complete the octahedral coordination The MnÐO5 distance (Table 1) is comparable to those in Mn II ±water complexes (Okabe & Koizumi, 1997;Hao et al, 2000;Ma et al, 2002;Schlueter & Geiser, 2003).…”
Section: Commentmentioning
confidence: 60%
“…Having potential donor oxygen and nitrogen atoms, dipicolinic acid has attracted the scientists from the coordination chemistry, and a number of studies have been carried out with dipicolinate (dpc) ligand by both inorganic and bioinorganic chemists during the past few years [3,4]. Dipicolinates commonly coordinate to transition metals by either carboxylate bridges between metal centers, to form polymeric or dimeric complexes [5][6][7], or tridentate (O, N, O 0 ) chelation to one metal ion [8][9][10]. The dipicolinic ligand with Cu(II) ions commonly has one or two coordination modes.…”
Section: Introductionmentioning
confidence: 99%